Proceso de atención de enfermería en paciente gestante con preeclampsia severa - Pardo Castillo, Cristina Del Cisne; Sanchez Pucha, Veronica Elizabeth (Machala : Universidad Técnica de Machala, 2019)
Introduction: Preeclampsia in pregnant women is a hypertensive syndrome, which occurs after 20 weeks of gestation, the main clinical manifestations are: hypertension 140/90 mmHG, proteinuria and edema, if the patient does not receive the diagnosis and treatment timely the picture can get complicated and develop Hellp syndrome. The World Health Organization states that the incidence is 2.8% in pregnant adolescents who suffer from preeclampsia, in Ecuador with a percentage of 10 to 15% and globally from 2 to 10%. Case presentation: 17-year-old pregnant woman goes to the gynecological emergency service of Teofilo Davila General Hospital, due to pelvic abdominal pain, headache, uterine contractions, mucous plug removal and lower limb edema, she is hospitalized in the gynecology department with diagnosis of pregnancy of 39 weeks of gestation + severe preeclampsia, after being assessed by resident is transferred to obstetric center with diagnosis of pregnancy of 39 weeks of gestation + lab labor latent phase + commitment of fetal well-being + Hellp syndrome, performed an emergency caesarean, obtaining a male newborn in good clinical condition. General Objective: To analyze a clinical case of a patient with severe preeclampsia that was treated in the Teófilo Dávila Hospital, through the review of clinical history and high-impact scientific articles for the application of the nursing care process. Method: The methods used for this case analysis were the qualitative study because it is based on the collection of data from the clinical and descriptive history because the characterization of the pathology is stated, as well as a bibliographic review of high impact scientific articles. the years 2014 - 2018 of indexed magazine as scielo, redalyc, dialnet. Result:It was found that a trigger to originate the pathology greatly intervene risk factors such as hereditary, nutritional lifestyles, age, parity mentioned by the authors Yoset Muñoz and Sánchez. The clinical symptoms that were found in the patient were arterial hypertension 140/90 mmHG, pelvic abdominal pain, headache, proteinuria, edema in lower limbs are considered warning signs of preeclampsia, being related to the results of the author Luis Beltran, while Elvia Merizalde mentions that the clinical manifestations that can occur during pregnancy are: arterial hypertension, edema in upper and lower limbs, may or not present proteinuria. Conclusion: The main obstetric complication that occurred in the patient was Hellp syndrome, this being a problem that generated a high rate of maternal and fetal morbidity and mortality with a rate of 5-8%; it is necessary in the process of nursing care to strengthen the care plans and the applicability of the basic needs of Virginia Henderson in relation to the altered domains of the patient. The nursing staff is trained to provide comprehensive care with quality and warmth.
Introducción: La preeclampsia en las gestantes es un síndrome hipertensivo, que se presenta a partir de las 20 semanas de gestación, las principales manifestaciones clínicas son: hipertensión arterial 140/90 mmHG, proteinuria y edema, si la paciente no recibe el diagnóstico y tratamiento oportuno el cuadro puede llegar a complicarse y desarrollar síndrome de Hellp. La Organización Mundial de la Salud declara que la incidencia es de 2.8 % en las adolescentes gestantes que padecen de preeclampsia, en el Ecuador con un porcentaje del 10 al 15 % y a nivel mundial del 2 al 10 %. Presentación de caso: Gestante de 17 años de edad acude al servicio de emergencia ginecológica del Hospital General Teofilo Davila, por presentar dolor abdominal pélvico, cefalea, contracciones uterinas, eliminación de tapón mucoso y edema en miembros inferiores, es hospitalizada en el servicio de ginecología con diagnóstico de embarazo de 39 semanas de gestación + preeclampsia severa, luego de ser valorada por residente es trasladada a centro obstétrico con diagnóstico de embarazo de 39 semanas de gestación + labor de parto fase latente + compromiso de bienestar fetal + síndrome de Hellp, realizándose una cesárea de emergencia, obteniendo un recién nacido de sexo masculino en buenas condiciones clínicas. Objetivo General: Analizar un caso clínico de una paciente con preeclampsia severa que fue atendida en el Hospital Teófilo Dávila, mediante la revisión de historia clínica y artículos científicos de alto impacto para la aplicación del proceso de atención de enfermería. Método: Los métodos utilizados para este análisis de caso fueron el estudio cualitativo porque se basa en la recopilación de datos de la historia clínica y descriptivo porque se enuncia la caracterización de la patología, también se realizó la revisión bibliográfica de artículos científicos de alto impacto de los años 2014 – 2018 de revista indexadas como scielo, redalyc, dialnet. Resultado: Se encontró que un desencadenante para que se origine la patología intervienen de gran manera los factores de riesgo como hereditarios, estilos de vida nutricionales, edad, paridad que mencionan los autores Yoset Muñoz y Sánchez. Las cuadro clínico que se encontró en la paciente fueron hipertensión arterial 140/90 mmHG, dolor abdominal pélvico, cefalea, proteinuria, edema en miembros inferiores son consideradas signos de alarma de la preeclampsia encontrándose relacionado con los resultados del autor Luis Beltran, mientras que Elvia Merizalde menciona que las manifestaciones clínicas que se puede presentar durante la gestación son: hipertensión arterial, edema en miembros superiores y inferiores, puede o no presentar proteinuria. Conclusión: La principal complicación obstétrica que se presentó en la paciente fue el síndrome de Hellp, siendo este un problema que generó un alto índice de morbimortalidad materno – fetal con un índice 5- 8 %; es necesario en el proceso de atención de enfermería fortalecer los planes de cuidados y la aplicabilidad de las necesidades básicas de Virginia Henderson en relación a los dominios alterados de la paciente. El personal de enfermería está capacitado para brindar una atención integral con calidad y calidez.
Keywords: PREECLAMPSIA SEVERA; SINDROME DE HELLP; GESTANTE; PRIMIGESTA